Effect of treatments for depression on quality of life: a meta-analysis*. Issue 4 (4th July 2017) - Hofmann, Stefan G.; Curtiss, Joshua; Carpenter, Joseph K.; Kind, Shelley
Abstract: Cognitive-behavioral therapy (CBT) and selective serotonin reuptake inhibitors (SSRIs) are the two first-line treatments for depression, but little is known about their effects on quality of life (QOL). A meta-analysis was conducted to examine changes in QOL in adults with major depressive disorder who received CBT (24 studies examining 1969 patients) or SSRI treatment (13 studies examining 4286 patients) for their depression. Moderate improvements in QOL from pre to post-treatment were observed in both CBT (Hedges' g = .63) and SSRI (Hedges' g = .79) treatments. The effect size remained stable over the course of the follow-up period for CBT. No data were available to examine follow-ups in the SSRI group. QOL effect sizes decreased linearly with publication year, and greater improvements in depression were significantly associated with greater improvements in QOL for CBT, but not for SSRIs. CBT and SSRIs for depression were both associated with moderate improvements in QOL, but are possibly caused by different mechanisms.